The Role of Safety Culture in Empowering Safety Behavior at Rail Transport Industry in Malaysia: A Review of Literature - Noorliza, Omar; Isha, Ahmad Shahrul Nizam (Journal of Social Transformation and Regional Development, 2023)
The awareness on safety culture and behavioral safety is in higher demand to reduce occupational incidents. For instance, safety culture is an essential element that could influence employees’ occupational behavior. The increasing number of passengers over the past few decades is evidence of the rapid regional development facilitated by the expansion of the railway industry. It has been implemented to alleviate congestion on highways and airways, as well as to promote global efforts to cut the emissions and employ sustainable energy. However, the inadequacies in the railway industry’s safety culture implementation led to a number of events, including train derailments and collisions, which has contributed to an increase in the rate of occupational accidents. Therefore, the objective of this study is to review the literature on the safety culture as a role in empowering the behavior of railway employees towards safety performance. Thus, the quantitative research design will be conducted through close-ended questionnaire. The sample of this study consist on employees that working in Malaysian rail transport industry. Therefore, SmartPLS will be used to test the model. Moreover, the findings expected to acknowledge an extensive literature review to propose a conceptual framework. It will be accomplished through integrating safety culture into the perceptions of workers, which is expected to influence their safety behavior at workplace. Thus, the Malaysia rail transport industry and related party can use this study as recommendations to improve their safety culture practices.